I’jazul Qur’an dalam QS. al-Mu’minun Ayat 14: Kajian ‘Alaqah dan Mudgah di Era Modern - Stevani Elenia (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2023)
I'jazul Qur'an is the appearance of a matter in Allah's revelation, so that it functions to weaken another matter which tries to compete with the revelation from Allah. I'jazul Qur'an has several miraculous aspects, including linguistic, scientific and legal aspects. One of the objects of study of I'jazul Qur'an which still exists today is I'jazul 'ilmi which focuses more on the scientific miracle side. This research aims to examine in more depth I'jazul 'ilmi relating to human embryology. The approach used is qualitative with data collection methods in the form of literature studies. Based on research results, it is known that 'alaqah and mudgah are part of the human development process before being born into the world. 'Alaqah in Arabic is interpreted as a leech, while modern technology has proven that 'alaqah is shaped like a leech. Meanwhile, mudgah is mentioned in the Koran as something that is chewed, and modern scientists have also proven with their technology that the mudgah process is like something that is chewed too. The existence of this can be concluded as evidence of the miracles of the Koran.